Ensinar, vigiar e punir: práticas educativas e disciplina militar (Portugal e América portuguesa - 1762-1777) - Francis Albert Cotta Formiga (2020)
In the mid-18th century, Europe was involved in the Seven Years' War (1756-1763). As a result of those conflicts, Franco-Spanish troops invaded the Portuguese territory. A modernization of the Portuguese military organization became urgent. Thus, a great remodeling took place, developed by the anglo-germanic Count Wilhelm of Schaumburg-Lippe. To accomplish the Lippe’s guidelines, his military writings on “military discipline” were a main source. In the view of this scenario, this paper pursued to answer the following question: How the extents and efforts of instrumentalization of this Military discipline guided the educational military practices in Portugal as well as in the Portuguese America, in the second half of the 18th Century. In search of those answers, we describe the dimensions and the operative propositions on “military discipline” issued from the Count of Lippe’s writings. To this end, the construction of a “military discipline” and its dimensions were interpreted based on Lippe's personal trajectory and socio-cultural context, marked by his family and sociability networks, his schooling, his experiences as a military man, ruler, and the creator of a Military Academy. We identified, in his writings and actions, what knowledge was chosen in order to be transmitted, which materials and methods were used in the learning-teaching process, what subjects were involved in the educational practices, as much as when and where to allocate them. Then, we analyzed how the administrators and military commanders in the Portuguese America took the Lippe’s writings and/or ideas. In methodological terms, we used “sets of analysis scales”. The writings and the military men were treated as “cultural mediators” inserted in the “writing cultures”, in a dynamic of knowledge and people circulation. The observation scale variation permitted to go from one story to another, without losing the singularities, the negotiations, the intentionalities and the subjectivities of the actors. Those aspects can be observed by means of visual-oral-written cultures, and the material elements of the military culture. From the sources’ interpretation (“military writings”, correspondence and iconography) we noticed that the military discipliners conducted the educational practices and were sustained by the tripod teach-watch-punish. In the beginning, it was needed to teach laws and regulations, which provided the knowledge about the utility and the military conduct. Afterwards, it was needed to watch the behaviors by a grid of pluridirectional eyes involving hierarchically superiors, partners and subordinates. Finally, it was needed to punish the transgressors who contradicted the conducts expected for the “good and loyal [military] vassal”. The dimensions of military discipline, based on the principles proposed by Count de Lippe, would have an echo in Portuguese America, making it possible to identify them in educational practices that can be perceived in material elements of military culture, such as drawings, plans, maps and books. They are fragments that allow the proof of educational legacies in different times and spaces.